Effectiveness of sorafenib dose modifications on treatment outcome of hepatocellular carcinoma: Analysis in real‐life settings. Issue 7 (31st March 2020) - Tak, Kwon Yong; Nam, Hee Chul; Choi, Jong Young; Yoon, Seung Kew; Kim, Chang Wook; Kim, Hee Yeon; Lee, Sung Won; Lee, Hae Lim; Chang, U Im; Song, Do Seon; Yang, Jin Mo; Kwon, Jung Hyun; et al.
Abstract : Controlling adverse events (AEs) through dose reduction can enhance drug adherence and treatment response. Currently, there is no guide for sorafenib dosing. The aim of this study was to evaluate whether sorafenib dosing could affect treatment outcomes. A total of 782 hepatocellular carcinoma (HCC) patients treated with sorafenib were evaluated for sorafenib dosing and its modifications via medical records at baseline and regular follow‐up. Study outcomes included progression‐free survival (PFS), overall survival (OS), sorafenib duration, cumulative dose, AEs and drug discontinuation. The median patient survival was 7.7 months. Overall, 242 (30.9%) patients underwent dose reduction and 121 (17.5%) discontinued sorafenib due to AEs. In multivariate analysis, dose reduction was identified to be independently predictive of PFS and OS. The 800‐to‐400 mg/day group provided significantly better PFS than the 800 mg/day‐maintained group or the 800‐to‐600 mg/day group. Likewise, the 800‐to‐400 mg/day group resulted in a significantly better OS than other dosing. However, dose reduction to 200 mg/day led to significantly worse PFS and OS. Hand‐foot skin reaction and drug discontinuation due to AEs were higher in the 800‐to‐600 mg/day group than the 800‐to‐400 mg/day group. The 800‐to‐400 mg/day group had significantly longer treatment duration and higher cumulative dose than the 800 mg/day‐maintained group. Sorafenib dose reduction can improve HCC survival and increase patient tolerance and adherence coupled with longer duration and higher cumulative dose. Dose reduction from 800 to 400 mg/day than to 600 mg/day is recommended when clinically warranted. However, dose reduction to 200 mg/day is not recommendable. Abstract : What's new? Although sorafenib, a kinase inhibitor drug, is effective in the treatment of advanced liver cancer, a large fraction of patients discontinue treatment because of adverse events. Here the authors evaluated the effect of drug dosing on treatment outcome in a large cohort study in South Korea. They found that proper sorafenib dose reduction helped control adverse events, leading to increased patient adherence coupled with longer duration and ultimately improved patient survival. They propose that proper dose modifications are a key determinant of successful sorafenib treatment.